PENGARUH BEBAN PENDINGIN TERHADAP KINERJA MESIN PENDINGIN DENGAN REFRIGERANT R134a DAN MC134 - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
Direct replacement method refrigerant in the engine manifold coolant HFC R134a with hydrocarbon widely developed. Retrofit refrigerant in cooling machine is not known with certainty the optimal pressure on the compressor, resulting in evaporation temperature and shows the performance of air conditioner. This study aims to determine the effect on the performance of the cooling load of air conditioner using refrigerant R134a and MC 134 on the filling pressure of the refrigerant which is optimal. The parameters were observed in this study was the effect of optimal pressure on kompessor, temperature condenser, evaporator temperature, the cooling load on the performance of refrigeration. Experimental research is still done on a laboratory scale. The result showed that if the cooling load increases will take effect on increasing the amount of heat absorbed by the evaporator, the evaporator heat discharged, reduced compressor work, the mass of refrigerant in the system and COP decreased. The use of hydrocarbon refrigerant MC 134 positive impact of heat absorbed the increase in the evaporator, the heat rise in dumped konsendor, COP system, the mass of refrigerant circulating in the system is reduced and the compressor work will decrease. Retrofit refrigerant hydrocarbon refrigerant R134a with MC 134 is worth considering for a vapor compression refrigeration system.